ANALYSIS OF THE INFLUENCE OF REGIONAL OWN-SOURCE REVENUE (PAD), CAPITAL EXPENDITURE, AND LABOR FORCE PARTICIPATION RATE (TPAK) ON ECONOMIC GROWTH IN BALI PROVINCE - Lydia Jane Natalia Toelle; Putu Krisna Adwitya Sanjaya (Adisam Publisher, 2025)
A country's economic well-being can be assessed through its economic development. Economic development in a specific region can be measured by its economic growth. In this study, economic growth is indicated by the influence of Regional Own-Source Revenue (PAD), capital expenditure, and the Labor Force Participation Rate (TPAK). This research aims to determine (1) the simultaneous and partial effects of PAD, capital expenditure, and TPAK on economic growth, and (2) the dominant variable influencing economic growth. The data used in this study consists of secondary time series data from 2018 to 2023 across nine regencies/cities in Bali Province. Data analysis was conducted using panel data regression with the assistance of the Eviews 12 software. The results show that PAD, capital expenditure, and TPAK collectively influence economic growth in the nine regencies/cities in Bali Province during 2018–2023. PAD and capital expenditure have a positive and significant effect on economic growth in these areas. Meanwhile, TPAK also has a positive but statistically insignificant effect on economic growth. PAD is identified as the dominant variable influencing economic growth in the nine regencies/cities in Bali Province during 2018–2023. This study implies that local governments need to strengthen strategies to increase PAD through revenue innovations, strategically manage capital expenditure to promote key sectors such as tourism and MSMEs, and enhance the quality and productivity of the workforce to support more inclusive and sustainable economic growth.